Game-based learning in mathematics: effects on students' productive struggle, visuospatial reasoning, and problem-solving skills - Espiritu, Jeffrey N.
In the present study, the applicability of delivering novel tasks and mathematical problems through game-based learning was tested in a blended learning environment. Two groups of 32 Grade 10 students took part in the experiment for eight weeks. They were exposed to either the game-based learning or the conventional approach. Both approaches weren delivered using 5E learning cycle. The results of the study were discussed in terms of the level of students’ productive struggle, visuospatial reasoning, and problem-solving skills. Researcher-designed Productive Struggle Scale and Problem-Solving Skills Test were subjected to an evaluation by experts and pilot testing. The test for visuospatial reasoning was adopted from the work of Ramful et al. (2017). A convergent mixed methods design was used to present the results in conjunction with analyses of the struggle task and the transcript of focus group discussion. There was no significant difference between the two groups in terms of productive struggle as measured by the Productive struggle Scale. However, this results has some inflection points as disparities were observed between the results of the scale and the analysis of the focus group discussion and struggle tasks. The analysis of the struggle tasks and the focus group discussion gave the impression that the game-based learning has driven students to hold productive behavior more frequently than those who were not exposed, which compensated the struggle they experienced in solving challenging tasks. Both approaches were bshwon to be equally effective in improving the over-all level of students’ visuospatial reasoning and mental rotation as measured by the Spatial Reasoning Instrument. The analysis performed on the transcript of the focus group discussion and struggle tasks was unable to establish a valid comparison as there were insufficient occasions when students from each group visually represented mathematical problems in the tasks. There was statistically significantimprovement in the test scores of the two groups as measured by the Problem-Solving Skills Test. With regards to specific mathemati cal content, the game-based group has a relatively superior performance in solving problems involving Polynomials and Polynomials Equations, however, no sigificant difference was found between the two conditions on Patterns and Sequences. The data set on struggle tasks and focus group discussion these results, suggesting that the game-based group has an advantage in terms of effort, completeness, accuracy in solutions, and the degree to which they iunderstood the problems in the tasks. As for the mediation and moderation tests, the path analyses showed that the effects of game-based learning on students’ problem-solving skills were not significantly mediated by productive struggle and/or visuospatial reasoning. The effect of game-based learning by productive struggle, visuospatial reasoning, and problem-solving skills was also found unrelated to one’s sex. Recommendations for classroom practice and instructional design were provided.